Public Bins : Singapore - Atelier HOKO (Temporary Press, 2022)
Atelier HOKO (2002) is an independent research lab that focuses on the study of the growing disengagement between people, things and space. Founded by Alvin Ho and Clara Koh. Atelier HOKO$1 (Bs encounters with public bins reveal how unexpected or (3z(Bimproper(3y (Buse or interactions, no matter how minor, are rich areas for study and observation, sometimes humorously so. This well describes the role of a street reporter, to make sense of phenomena on the streets and find delight and meaning in doing so. We hope readers will go on their own note-taking discoveries whenever they are on the way to dispose rubbish.s
English
Keywords: N4390-5098 Visual Arts. Exhibitions